The Effect of Varied Fartlek Method Exercises on VO2max and Specific Endurance in Young Football Players - Ahmed Qasim Kadhim (Pubmedia Jurnal Pendidikan Olahraga, 2025)
The research question stems from the importance of oxygen uptake (VO2max) and endurance performance for young football players and their impact on the skills and tactical performance of all players in the game. The researchers, who are experts in the field of sports training physiology, observed fluctuations in endurance performance levels and players’ boredom due to a lack of variety in training methods, including a variable-speed play method. This is because the researchers observed the training programs of some coaches at the Karbala Youth Club and found that most coaches rely on a training method that is repetitive and causes players to get bored. Another reason that prompted the researchers to address this issue was the increase in the speed of modern football games. This requires young football players to improve their endurance performance, allowing players to always be in the best condition and delay fatigue, thereby achieving good results. Therefore, the researchers conducted various fartlek exercises on young football players at the Karbala Holy Land Club. The sample was randomly selected from the community. The sample was divided into two groups (control and experimental groups) with ten players in each group. The aim was to determine the effects of these exercises on the study group. The researchers hypothesized that diversified fartlek exercises would have a positive impact on the development of specific endurance skills in young football players. After conducting a pretest and applying these exercises to the study subjects three times a week for ten weeks, the researchers conducted a posttest and obtained the results. These carefully prepared exercises demonstrated their positive impact on the study group